Association between online and offline social support and internet addiction in a representative sample of senior high school students in Taiwan: The mediating role of self-esteem. (July 2018) - Lin, Min-Pei; Wu, Jo Yung-Wei; You, Jianing; Chang, Kuei-Mien; Hu, Wei-Hsuan; Xu, Sian
Abstract: Based on the Sociometer Theory and DuBois' conceptual framework for the relations of perceived social support and self-esteem in adolescence, this study was designed to examine the mediating role of self-esteem in the relationship between online and offline social support and Internet addiction (IA) in a large representative sample of senior high school students in Taiwan. Using a cross-sectional design, 1922 participants (1019 females) were recruited from senior high schools using both stratified and cluster sampling, and a comprehensive survey was administered. Structure equation modeling and bootstrap analyses results showed that IA severity was significantly and negatively predicted by offline social support, and mediated through self-esteem. The results not only supported the Sociometer Theory, but were also consistent with the conceptual framework proposed by DuBois. Online social support positively predicted IA severity, but was unable to predict self-esteem. The mediating role of self-esteem in the relationship between online and offline social support and IA severity were discussed. Graphical abstract: Image Highlights: Offline social support negatively predicted IA. Self-esteem negatively predicted IA. Self-esteem mediates the relation of offline social support and IA. Mediation model supports the Sociometer Theory. Non-significant relation between online social support and self-esteem.